Depolymerization and mineralization rates at 12 Mediterranean sites with varying soil N availability. A test for the Schimel and Bennett model - Delgado-Baquerizo, Manuel; Gallardo, Antonio (Soil Biology and Biochemistry, 2011)
It has been suggested that the relative abundance of soil nitrogen forms should change along an N availability gradient. This model was originally described at a biome scale, and few studies have tested it at other scales. Moreover, none of them has examined whether changes in the relative rates of ammoniﬁcation, nitriﬁcation and depolymerization rates also occurs. Our goal was to test whether these N transformation rates change along an N availability gradient which is likely to exist between forest, shrubs and grasses. We used three N availability indexes (total K2SO4-extractable N, ion exchange membrane N and the sum of N mineralization and depolymerization rates). Depolymerization dominated over mineralization in the two poorest plant communities, while ammoniﬁcation and nitriﬁcation rates dominated in intermediate and nutrient rich plant communities respectively. These results conﬁrm that the Schimel and Bennett model can be applied at a regional scale, and that N availability may be modulating not only the dominant N form, but also the relative abundance of a particular N transformation rate.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Ammoniﬁcation rate; Nitriﬁcation rate; nitrogen cycle; soil ammonium; Soil DON; Soil nitrate

Dissolved Organic Nitrogen in Mediterranean Ecosystems - Delgado-Baquerizo, M.; Covelo, F.; Gallardo, A. (Pedosphere, 2011)
Dissolved organic nitrogen (DON) in soils has recently gained increasing interest because it may be both a direct N source for plants and the dominant available N form in nutrient-poor soils, however, its prevalence in Mediterranean ecosystems remains unclear. The aims of this study were to i) estimate soil DON in a wide set of Mediterranean ecosystems and compare this levels with those for other ecosystems; ii) describe temporal changes in DON and dissolved inorganic nitrogen (DIN) forms (NH+ 4 and NO− 3 ), and characterize spatial heterogeneity within plant communities; and iii) study the relative proportion of soil DON and DIN forms as a test of Schimel and Bennett’s hypothesis that the prevalence of diﬀerent N forms follows a gradient of nutrient availability. The study was carried out in eleven plant communities chosen to represent a wide spectrum of Mediterranean vegetation types, ranging from early to late successional status. DON concentrations in the studied Mediterranean plant communities (0–18.2 mg N kg−1 ) were consistently lower than those found in the literature for other ecosystems. We found high temporal and spatial variability in soil DON for all plant communities. As predicted by the Schimel and Bennett model for nutrient-poor ecosystems, DON dominance over ammonium and nitrate was observed for most plant communities in winter and spring soil samples. However, mineral-N dominated over DON in summer and autumn. Thus, soil water content may have an important eﬀect on DON versus mineral N dominance in Mediterranean ecosystems.
The following values have no corresponding Zotero field: publisher: Soil Science Society of China
Keywords: dissolved inorganic nitrogen; nitrogen cycle; soil ammonium; soil N availability; soil nitrat

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism